A rapid LC–MS/MS quantification of peramivir using a simple and inexpensive sample precipitation: application to PK. (February 2015) - Wang, Zhan-Zhang; Zhang, Ming; Shang, De-Wei; Ni, Xiao-Jia; Hu, Jin-Qing; Qiu, Chang; Wen, Yu-Guan
Aim: Peramivir is a newly approved selective neuraminidase inhibitor designed to inhibit influenza virus infection.Methodology/results: We report a robust and sensitive method utilizing simple precipitation extraction with LC–MS/MS for the high-throughput quantification. Addition of 0.06 M of ammonium formate and 0.1% formic acid in mobile phase could help reduce the matrix effect. This method uses 100 µl of plasma and covers a linear concentration range from 5 to 10, 000 ng/ml. Other validation parameters are also evaluated and meet regulatory expectations by US FDA guidelines.Conclusion: The developed HPLC–MS/MS method has been successfully applied to support a clinical pharmacokinetic study. The strategy presented here can be applied elsewhere and may be useful for other amphiphilic drugs.